Pengaruh User experience Terhadap Customer Satisfaction dengan E-service quality Sebagai Mediator pada Blibli: A Conceptual Paper - Gusfi, Dhiya Athaya; Widodo, Arry; Dewi, Citra Kusuma; Rubiyanti, Nurafni; Silvianita, Anita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The rapid development of the internet in Indonesia is driving the growth of e-commerce. Blibli, one of the leading e-commerce platforms, has experienced fluctuations in the number of visits in recent years. This study aims to investigate the relationship between User experience (UX), Customer Satisfaction (CS), and E-service quality (ESQ) among Blibli consumers in Indonesia. This study uses a correlational approach used to analyze data collected from all consumers who have made at least one Blibli purchase in Indonesia. The research sample was selected using the purposive sampling method, which involves incorporating certain criteria into the sampling process. The Partial Least Square (PLS) approach to Structural Equation Modeling (SEM) was used to analyze the data.